Problems with Repeated Measures Analysis: Demonstration with A Study of the Diversification and Performance Relationship - Bergh, Donald D. (Academy of Management Journal, 1995)
This study reviews how repeated measures analysis has been applied and discusses alternative approaches for that type of analysis. A content analysis of 86 repeated measures studies showed a lack of (1) control for violations in data assumptions, (2) tests of characteristics of differences in measurement means, and (3) full tests of multivariate models. Further, an analysis of diversification and performance in 40 firms showed that empirical results and theory development can vary according to how repeated measures analysis is performed. Suggestions for research using repeated measures analysis are offered.